2017
DOI: 10.1001/jamaneurol.2016.5374
|View full text |Cite
|
Sign up to set email alerts
|

Combined Intravenous Thrombolysis and Thrombectomy vs Thrombectomy Alone for Acute Ischemic Stroke

Abstract: IMPORTANCE Mechanical thrombectomy (MT) improves clinical outcomes in patients with acute ischemic stroke (AIS) caused by a large vessel occlusion. However, it is not known whether intravenous thrombolysis (IVT) is of added benefit in patients undergoing MT.OBJECTIVE To examine whether treatment with IVT before MT with a stent retriever is beneficial in patients undergoing MT. DESIGN, SETTING, AND PARTICIPANTSThis post hoc analysis used data from 291 patients treated with MT included in 2 large, multicenter, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
131
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 203 publications
(143 citation statements)
references
References 23 publications
7
131
2
3
Order By: Relevance
“…In the present study, age and admission NIHSS were identified as prognostic factors on multivariate analyses but treatment allocation did not influence outcome. This is in agreement with a smaller single-center pilot study that examined the effects of bridging versus dEVT on outcome and found no such impact [18] as well as with several other retrospective studies [22,23,[33][34][35] and prospective registry data [20,21,24] that did not find differences in outcome between patients treated with bridging and those treated with dEVT. In contrast, other retrospective studies found lower mortality rates [23], lower symptomatic hemorrhage rates and higher reperfusion rates in patients treated with dEVT [36] while two meta-analyses on the subject found evidence for lowering mortality and severe disability rates with bridging [26,37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, age and admission NIHSS were identified as prognostic factors on multivariate analyses but treatment allocation did not influence outcome. This is in agreement with a smaller single-center pilot study that examined the effects of bridging versus dEVT on outcome and found no such impact [18] as well as with several other retrospective studies [22,23,[33][34][35] and prospective registry data [20,21,24] that did not find differences in outcome between patients treated with bridging and those treated with dEVT. In contrast, other retrospective studies found lower mortality rates [23], lower symptomatic hemorrhage rates and higher reperfusion rates in patients treated with dEVT [36] while two meta-analyses on the subject found evidence for lowering mortality and severe disability rates with bridging [26,37].…”
Section: Discussionsupporting
confidence: 90%
“…Several recent studies looked at individual or pooled data from recent observational or randomized studies yielding conflicting results [20][21][22][23][24][25][26]. Thus, while most did not find differences in outcome between dEVT and bridging [20,22,24], some found advantages for dEVT [21,25], while still others were able to detect benefit for bridging over dEVT [26]. In a recent topical review article summarizing the data up to date, there were no conclusive recommendations that could be drawn regarding which strategy was better but it was noted that dEVT may be noninferior to bridging [27].…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, we chose to include only patients treated with IV thrombolysis prior to thrombectomy, given that the potential benefit of admission to the closest primary stroke center is to offer IV thrombolysis sooner. Some authors reported similar thrombectomy outcomes with and without thrombolysis [17,18]. However, a recent meta-analysis demonstrated that patients treated by bridging therapy have better functional outcomes and lower mortality, without increasing symptomatic ICH risk compared with patients treated with mechanical thrombectomy alone [19].…”
Section: Discussionmentioning
confidence: 99%
“…A large majority supported bypassing ACH when LVO was suspected despite the lack of randomized controlled trial proving that such a model would improve outcomes for LVO cases and not significantly penalize non-LVO patients delayed in receiving IV tPA by mistriage. This indicates that the responders believed that endovascular therapy is the optimal treatment modality for LVO patients with IV alteplase being less or even not important at all as suggested by a recent analysis [11]. The more surprising finding was that a sizable minority, 44%, supported triaging non-LVO case to the further ECH.…”
Section: Discussionmentioning
confidence: 92%